Intelligent MPPT control for SEPIC-Luo converter in grid tied photovoltaic system - Prasad, D. Thivya; Anandhakumar, R.; Balamurugan, P. (Institute of Advanced Engineering and Science, 2024)
Grid connected solar photovoltaic (SPV) systems are becoming more and more common due to steadily rising energy demand. The advantages of photovoltaic power generation, such as its eco-friendliness, low maintenance requirements, and lack of noise, are making it as a significant renewable energy source (RES). This framework presents the modeling and control design of PV grid tied system implemented with integrated single ended primary inductance (SEPIC) Luo converter. The main goal of this work includes investigating solar PV system behaviour and creating an effective grid connected solar power. Solar PV module tracks maximum power, with an aid of chaotic cascaded fuzzy a maximum power point tracking (MPPT) has developed. The DC voltage obtained is fed to 1Φ voltage source inverter (VSI) for conversion of AC voltage. In comparison to typical PWM control, the spectrum performance of the examined voltages is improved by adjusting the nominal duty cycle of main switch of SEPIC-Luo converter. So that PV output impedance is equivalent to DC-DC converter's input resistance. Finally, the obtained AC voltage is supplied to 1Φ grid for further applications. With less THD, an efficiency of 96% is achieved when the implementation of the suggested system is carried out using MATLAB/Simulink.